Cork oak (Quercus suber L.) acorn as a substitute for barley in the diet of rabbits; Effect on In vivo digestibility, growth and carcass characteristics. J. anim (Journal of Animal and Veterinary Advances, 2007)
In this study 2 experiments were conducted to evaluate the feeding value of cork oak acorn as an energy source for rabbits. Experiment 1 was a digestibility trial using 20 adult rabbits (10 rabbits/group) and experiment 2 was a growth performance and carcass evaluation using 24 growing rabbits in a completely randomised design. Two diets were formulated to contain either 250 g Dry Matter (DM) barley (Barley diet) or 250 g DM oak Acorn (Acorn diet)/kg and included mainly, wheat bran, soybean meal, hay, molasses, calcium phosphate, Cu SO4 and salt. Inclusion of acorn in the diet did not result in any change in odour and fungal contamination nor in the feed intake (p>0.05). However, acorn in the diet decreased the in vivo digestibility by 10.8, 11.5 and 17.5%, respectively, for DM, Organic Matter (OM) and Crude Protein (CP). Although the rabbits fed acorn diet retained less nitrogen than those fed barley diet, they were positive in the nitrogen balance. The final live weight and daily weight gain from weaning through slaughter did not show any significant difference between rabbits fed the control diet and those fed the experimental diet. Similar carcass yield and feed conversion ratio were observed for the 2 groups. Weight of full gastrointestinal, liver, kidney and caecum were not affected (p>0.05) by the presence of acorn in the experimental diet. A more careful evaluation of the real content and digestibility of nutrients from acorn is necessary to evaluate their nutritional value before considering them as a potential feed for rabbits.